The PERSUADING FACTORS TO THE OPERATOR OF THE ACCRUAL BASIC APPLICATION SYSTEMAT WORKING UNIT IN THE REGIONAL KPPN TEBING TINGGI WITHHUMAN RESOURCE QUALITY AS THE MODERATED VARIABLE INPUT - Afrina, Ade Pulungan (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the study was to examine the influence of system quality, information quality and service quality on users’ satisfaction of accrual basic application system (SAIBA) at work unit in the regional  payment of KPPN Tebing Tinggi with human resource quality as moderating variable. The datas were analyzed by Structural Equation Modeling Partial Least Squares (SEM PLS). The result of this study showed that system quality, information quality, service quality and human resource quality had positive significant influence on the users’ satisfaction of SAIBA’s application. Human resource quality as moderated variable could moderate the relationship between system quality and information quality with the users’ satisfaction of SAIBA’s application, but it could not moderate the relationship between service quality with the users’ satisfaction of SAIBA’s application.